Analysis of Cocoa Bean Inventory Control with Continuous (Q) and Periodic (P) Review System Methods at Majapahit Chocolate Factory - Tuffahati, Shaffa Arindra; Pulansari, Farida (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Majapahit Chocolate Factory is one of the manufacturing industries that processes cocoa beans into various chocolate products called Majapahit Chocolate. In the production process, Majapahit Chocolate Factory has not controlled raw material inventory efficiently using any method so there is still a frequent mismatch between the amount of inventory and production needs. The higher the amount of inventory, the higher the inventory costs incurred. Based on these problems, this study aims to determine the control of cocoa bean inventory to minimize the total cost of inventory at the Majapahit Chocolate Factory. The results showed that the most minimal total inventory cost was the Continuous Review System method of IDR303,863,596.70 with a savings of 1% from the Periodic Review System method and 4% from the company method. After forecasting the need for raw materials for January-December 2023 using the Weighted Moving Average method, the total demand for cocoa beans during the 2023 period is 61752 kg. Meanwhile, the size of the order quantity is 5739 kg and the reorder point is 8234 kg, so the total inventory cost required in January-December 2023 is IDR1,278,081,375.44.